EFISIENSI PERTUMBUHAN LABA BERDASARKAN PERPUTARAN KAS, PERPUTARAN PIUTANG DAN PERPUTARAN PERSEDIAAN PADA PT MAYORA INDAH TBK PERIODE 2014-2023 - Sabili, Jihad; Achmad Ludvy (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to analyse the efficiency of profit growth at PT Mayora Indah Tbk during the 2014-2023 period by reviewing three main indicators, namely cash turnover, accounts receivable turnover, and inventory turnover. The method used is quantitative research. The data used is secondary data in the form of financial statements of PT Mayora Indah Tbk for the period 2014-2023. The analysis method used is descriptive statistical test, frontier regress test, hypothesis testing with z test and chi wald test and efficiency test using Stata version 14. The results of the z value research 3.96 with a P>|z| value of 0.000 < 0.05 partially show that Cash Turnover has a significant effect on Profit Growth, z value -1. 95 with a P >|z| value of 0.051> 0.05 partially Accounts Receivable turnover has no significant effect on profit growth, zcount value -1.30 < ztabel 1.96 with a P >|z| value of 0.195 > 0.05 partially inventory turnover has no significant effect on profit growth. While the value of wald chi2 (3) = 15.76 with a prob value = 0.0013 <0.05 means that simultaneously Cash Turnover, Receivables Turnover and Inventory Turnover have a significant effect on Profit Growth Efficiency.